2021
DOI: 10.3390/ijerph18041567
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Back Pain and Associated Risk Factors among Nurses at King Abdulaziz University Hospital

Abstract: Aim: To determine the prevalence of LBP and the associated risk factors among nurses at King Abdulaziz University Hospital (KAUH). Methods: A cross-sectional study design was adopted with a convenience sample of 234 nurses recruited from nine different departments at KAUH in Jeddah, Saudi Arabia. Participants completed the questionnaire, which had two parts: Part I: Socio-demographic data, medical factors, and work-related factors; and Part II: Standardized Nordic Musculoskeletal Questionnaire was used to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
9
10
2
Order By: Relevance
“…In our study, years of work experience were found to be significantly related to LBP. This finding is consistent with a study that discovered nurses with 5 years of experience were three times more likely to suffer from LBP 4,26,36) . This is because nurses are more likely to face physical and psychological hazards throughout their careers 26) .…”
Section: Risk Factors Of Lbp In Middle Age Adultsupporting
confidence: 92%
“…In our study, years of work experience were found to be significantly related to LBP. This finding is consistent with a study that discovered nurses with 5 years of experience were three times more likely to suffer from LBP 4,26,36) . This is because nurses are more likely to face physical and psychological hazards throughout their careers 26) .…”
Section: Risk Factors Of Lbp In Middle Age Adultsupporting
confidence: 92%
“…(38) Higher cortisol levels are associated with a lower strength of lumbar muscles, resulted in LBP. (6,34) Our study results con rmed that working time was signi cantly associated with LBP. This fact correlates with a study that focused on nurse, that 5 years of experiences nurses were 3 times more likely to experience LBP.…”
Section: Discussionsupporting
confidence: 70%
“…(2) Exercise reduces stress and the level of cortisol which increases in stress conditions. (34)(35)(36) Other studies have reported that strengthening the spinal muscles by exercises such as stretching or aerobic training decreases LBP by 30% in terms of intensity of pain and disability. (26) The result of this study suggested that the severity of stress had a signi cant correlation with low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is critical to raise OHS awareness among nurses about the serious physical injury that can arise from work-related musculoskeletal problems [10]. Almaghrabi and Alsharif [3] conducted similar research at King Abdulaziz University Hospital in Saudi Arabia to determine the prevalence of Low Back Pain (LBP) and related risk factors among nurses. A cross-sectional strategy was used to recruit a convenience sample of 234 nurses.…”
Section: Impact Of Physical Factorsmentioning
confidence: 99%